Reflection of the effect of empowering leadership behaviors on the workforce agility (An analytical study of the opinions of teachers in the private schools of the Diwaniyah governorate center) - ShaymaSaedWdaah AL-Ganemi, Professor Dr.Ihssan Dahash Chalab, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aimed to test the effect of empowering leadership behaviors expressed with its dimensions (leadership by example, participatory decision-making, training, information exchange, showing interest with others) on workforce agility (flexibility, adaptation ,proactivity) in private schools in Al-Diwaniyah Governorate,and the problem was summarized with a set of questions based on the researcher’s perceptions, the most important of which resulted in the statement of the influence that empowering leadership behaviors exert on workforce agility, and for achieve the objectives of the study, a hypothetical scheme was designed that embodies the nature of the relationship between the variables included in the study, and a set of hypotheses were built aimed at identifying The level of the relationship between empowering leadership behaviors and workforce agility in private schools in Al-Diwaniyah Governorate, and the study relied on the nature of the questionnaire as a main tool in collecting data and information from a sample of (273) faculty members, and the study used a set of statistical programs represented in (SPSS). V.26 & AMOS.V.26) in order to reach the results that the study aspires to answer, using several statistical methods, especially in (the arithmetic mean, standard deviation, relative importance, coefficient of variation, t-test, simple correlation coefficient, and the structural equation modeling(.